Tinjauan Yuridis Terhadap Ketidakstabilan Harga Beras Ditinjau Dari Undang-Undang Nomor 8 Tahun 1999 Tentang Perlindungan Konsumen - Angkak, Andreas Anandri Bagus; Mauritsius, Darius; Jacob, Yossie M Y (Law Faculty, Nusa Cendana University, 2024)
This research aims to find out legal protection for consumers as well as the inhibiting factors in efforts to stabilize rice prices in terms of Law Number 8 of 1999 concerning Consumer Protection. The research method used in this research is Normative Juridical, meaning research conducted to analyze data in literature using currently applicable legal regulations. The legal sources and materials used are primary, secondary and tertiary legal materials. The research results show that the price of rice has experienced significant price fluctuations in recent years, this is due to factors such as decreasing rice production but increasing demand for rice. So the government is making every effort to overcome this problem in order to protect the public, especially consumers who have difficulty getting or buying rice at quite high prices. There are two ways of protection carried out by the government, namely preventive and repressive protection.